Identity-based puncturable signature scheme - Dongmei YANG; Yue CHEN; Jianghong WEI; Xuexian HU (Tongxin xuebao)
To overcome the shortcomings of available forward-secure identity-based signature （IBS） scheme in terms of actual practicability and secret key update efficiency， the notion of identity-based puncturable signature （IBPS） scheme was proposed based on the idea of puncturable public-key encryption scheme.Specifically， the syntax and security notion of IBPS were given， and then a concrete IBPS scheme was constructed based on Bloom filter.Under the computational Diffie-Hellman assumption， the proposed scheme achieved the existential unforgeability in the random oracle model.The performance analysis and implementation results demonstrate that， compared with traditional forward-secure IBS schemes， the proposed scheme provides more practical fine-grained forward secrecy， and has higher efficiency of secret key update.